English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

2006-12-07 08:47:03 · 11 answers · asked by Brittany M 1 in Science & Mathematics Mathematics

11 answers

5x³+9x² - 2x = 0
x(5x² + 9x - 2) =0
x(5x - 1)(x + 2) = 0
x = 0 or x = 1/5 or x = -2

2006-12-07 08:51:15 · answer #1 · answered by Jim Burnell 6 · 1 0

I'm guessing solve for x.

Make one side of the equation equal zero as any number times zero is zero. so take away 2x from each side.

5x^3 + 9x^2 - 2x = 0

Left hand side has an obvious common factor of x

x (5x^2 +9x -2) = 0

Need to factorise the bracketed expression. I see that it is -2 so the signs in the brackests must be a plus and a minus. Also that the 5 and two are prime so that we must have 5 and 1 as the multipliers of x and 1 and 2 as the single numbers. trial and error quickly gives


x (5x-1) (x+2) = 0

so for this expression to be true then either

x=0
(5x-1)=0 i.e. 5x=1 i.e. x=0.2
or
(x+2)=0 i.e. x=-2

so x = -2, 0, 0.2 are all possible solutions

2006-12-07 16:59:04 · answer #2 · answered by crazy_tentacle 3 · 0 0

5x³ + 9x² = 2x --- Subtract 2x from both sides...
5x³ + 9x² - 2x = 0 --- Factor x from each term...
x(5x² + 9x - 2) = 0 --- Fctor the trinomial...
x(x + 2)(5x - 1) = 0 --- One of our three terms must equal 0, solve for all three...
x = 0 --- Plain and simple...
x + 2 = 0 --- Subtract 2 from each side...
x = -2
5x - 1 = 0 --- Add 1 to both sides...
5x = 1 --- Divide both sides by 5...
x = (1/5)

ANSWER: x = 0, x = -2, or x = 1/5

CHECK:
5(0³) + 9(0²) = 2(0)
0 + 0 = 0
0 = 0 --- x = 0 checks out...

5(-2³) + 9(-2²) = 2(-2)
5(-8) + 9(4) = -4
(-40) + (36) = -4
-4 = -4 --- x = -2 checks out...

5[(1/5)³] + 9[(1/5)²] = 2(1/5)
5(1/125) + 9(1/25) = (2/5)
(5/125) + (9/25) = (2/5)
(1/25) + (9/25) = (2/5)
(10/25) = (2/5)
(2/5) = (2/5) --- x = (1/5) checks out...

2006-12-07 17:09:34 · answer #3 · answered by Anonymous · 0 0

Your first step is to bring everything over to the left hand side.

5x^3 + 9x^2 - 2x = 0

****NOTE***** Do NOT divide by x; it is an invalid step in solving equations and you can eliminate values by doing so.

At this point, we factor out the greater term we can. In this case, it's x.

x(5x^2 + 9x - 2) = 0

Now, we solve the quadratic as normal. After much trial and error, you'll find that it factors like so:

x(5x - 1)(x + 2) = 0

Therefore, you have these set of equations
x = 0
5x - 1 = 0 ----> 5x = 1 -----> x = 1/5
x + 2 = 0 -----> x = -2

Therefore, x = 0, -2, 1/5

2006-12-07 16:53:02 · answer #4 · answered by Puggy 7 · 1 0

= 5x^3 + 9x^2 - 2x
= x (5x^2 + 9x - 2)
= x (5x - 1)(x + 2)

... if that's equal to 0:

x = 0, x = 1/5, x =-2

2006-12-07 16:51:31 · answer #5 · answered by Anonymous · 1 0

5x³+9x²=2x subtract 2x from each side
5x^3+9x^2-2x=0 factor out x
x(5x^2+9x-2)=0 factor the trinomial
x(5x-1)(x+2)=0
x=0

5x-1=0
x=1/5

x+2=0
x=-2

roots are: 0, 1/5, -2

2006-12-07 16:52:04 · answer #6 · answered by yupchagee 7 · 1 0

5x³+9x² - 2x = 0
x(5x² + 9x - 2) =0
x(5x - 1)(x + 2) = 0
x = 0 or x = 1/5 or x = -2

2006-12-07 17:18:01 · answer #7 · answered by Josh H 2 · 0 0

5x^3+9x^2-2x=0
x(5x^2+9x-2)=0
x(5x-1)(x+2)=0
x=0 or 5x-1=0 or x+2=0
S0 x=0, x=1/5, or x=-2

2006-12-07 16:52:02 · answer #8 · answered by martina_ie 3 · 1 0

x=0, 1/5, -2

2006-12-07 16:53:12 · answer #9 · answered by EnjoysCalculus 1 · 0 0

5x^3+9x^2-2x=0
x(5x^2+9x-2)=0
x(5x^2+10x-x-2)=0
x[5x(x+2)-1(x+2)]=0
x(x+2)(5x-1)=0
x=0 or x=-2 or x=1/5
setting each factor to zero

2006-12-07 16:51:27 · answer #10 · answered by raj 7 · 1 0

fedest.com, questions and answers